Diagnostic strategies in general practice and the emergency department: a comparative qualitative analysis. Issue 5 (1st June 2019) - Bösner, Stefan; Abushi, Jamal; Feufel, Markus; Donner-Banzhoff, Norbert
Abstract : Objective: We sought to explore differences and commonalities between diagnostic strategies used by clinicians in general practice and the emergency department. Design: Qualitative study. Settings: We videotaped 282 consultations of 12 general practitioners (GPs) in Germany, irrespective of presenting complaint or final diagnosis. Reflective interviews were performed after each consultation. In addition, 171 consultations of 16 emergency physicians (EPs) based at two tertiary care hospitals in the Midwest of the USA were observed, and their conversations recorded. Recordings of consultations and GP interviews were transcribed verbatim and analysed using a coding system that was based on published literature and systematically checked for reliability. Results: EPs more often considered acute and severe conditions, even if pretest probabilities were low. In contrast, GPs more often involved their patients in the decision-making process and provided assurance concerning their complaints. To focus their workup, EPs used a more directive style of interviewing including a high proportion of routine questions and rarely used open questions or active listening. Conclusions: Strategies used by physicians in both settings seem to be well adapted to their respective environments. Whereas the physician-led diagnostic process in the emergency department is well suited to rule out life-threating disease, diagnosis and appropriate treatment of everyday problems may require a more patient-centred style.